Determinants of migration and household member arrangement among poor rural households in China: The case of North Jiangsu. Issue 1 (18th November 2019) - Tang, Shuangshuang
Abstract: After decades of rural‐to‐urban migration, alleviating poverty among rural populations has become a priority of the central government of China. Migration is assumed to be a strategy for poor rural populations to cope with poverty. Nevertheless, extant research has paid little attention to migration determinants and household arrangements of poor rural populations in particular. Moreover, existing literature regarding migration in China from a household perspective is relatively scare. Therefore, based on a recent survey in North Jiangsu, China, this paper attempts to explore both migration determinants and the organisations of poor rural households in particular from a household perspective. The findings show that migration is an important livelihood strategy of poor rural households, triggered by limited farmland and major family events, which heavily relies on household structure and educational attainment of household members. In addition, it is observed that poor rural households adopt diversified strategies to arrange family members either within or outside the home village in order to boost household income. The findings reveal the importance of migration for poor rural households and the dilemmas that poor rural households tend to face. Reducing rural poverty in China requires policies that are more responsive to the needs of rural families for local employments, quality education, and long‐term insurance programmes.